"الأخطاء اللغوية في كتاب درس اللغة العربية للناشر "تيغا سرانكي - Erta Mahyudin; Mifta Dwi Kardo; Ubaid Ridlo (Kalimatuna: Journal of Arabic Research, 2023)
This research aims to reveal the forms of linguistic errors in Arabic Book published by Tiga Serangkai in terms of graphology, syntax and morphology errors. Researchers used qualitative research method, with the techniques to collect data are observation and interview, and the data analysis techniqe is content analysis. This research found some errors in terms of syntax such as “marfuat, mansubat,  majrurat”, incompatibilities between “mubtada” and “khabar”, “fiil” and “fa'il”, “ism isyarah” and “musyar ilaih” and errors in “idhafah”. Some errors in terms of morphology such as in “wazn fiil” and “wazn ism”. In terms of graphology such as errors in writing “hamzah qatha”, changing letters, deleting letters, and adding letters. After conducting the research, it has found that errors in this book occurred because the author of the book had not read the book contents in detail, lack of supervision from the editor, and the limitation of time.